2017
DOI: 10.33533/jpm.v10i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalensi Dan Faktor Risiko Tungau Debu Rumah Di Pamulang (Tangerang) Dan Pasar Rebo (Jakarta)

Abstract: House dust mites (HDM), anaeroallergen which may be found in all of part of the urban house including mattress. The objectives of this study were to find out the prevalence and risk factors of house dust mites in urban communities i.e.,Pamulang (Southern Tangerang) and Pasar Rebo (Nothern Jakarta). The study design was a cross-sectional study. The samples of house dusts were collected from house of respondents, living-room floors, bed-room floors, kitchen-room floors, terrace-room floors, ventilation, kapuk ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
4
0
3
Order By: Relevance
“…Microscopic examination on 52 dust samples taken from mattresses in this study showed that 49 (94%) of samples were positively infested by Dermatophagoides spp. As a tropical region, Indonesia had a relatively warm temperature 25-30 o C and high humidity (70-80%) which were beneficial for the growth and development of house dust mites (Subahar, 2016). Mattress was one of the most occupied and the least often replaced object in detention center, therefore it was rich in skin debris that was the main source of food for house dust mites.…”
Section: Resultsmentioning
confidence: 99%
“…Microscopic examination on 52 dust samples taken from mattresses in this study showed that 49 (94%) of samples were positively infested by Dermatophagoides spp. As a tropical region, Indonesia had a relatively warm temperature 25-30 o C and high humidity (70-80%) which were beneficial for the growth and development of house dust mites (Subahar, 2016). Mattress was one of the most occupied and the least often replaced object in detention center, therefore it was rich in skin debris that was the main source of food for house dust mites.…”
Section: Resultsmentioning
confidence: 99%
“…merupakan TDR yang tersebar secara kosmopolit dan banyak ditemukan di Indonesia, 26,27,28 terutama spesies Dermatophagoides pteronyssinus. 25,29,30 Penelitian dilakukan pada bulan Maret dimana Kabupaten Jember mengalami musim hujan dengan suhu berkisar antara 23º-26º dan kelembaban udara relatif meningkat. Pertumbuhan dan perkembangbiakan D. pteronyssinus dan D. farinae baik pada suhu 25º-30ºC dan kelembaban relatif 70-80%.…”
Section: Metode Penelitianunclassified
“…Selain itu, D. pteronyssinus memiliki perkembangbiakan yang lebih cepat dibandingkan TDR lainnya. 27,29,31 Dermatophagoides spp. lebih banyak ditemukan pada debu ruang tidur dibandingkan ruang tamu, begitu pula dengan kepadatan rata-rata Dermatophagoides spp.…”
Section: Metode Penelitianunclassified
See 1 more Smart Citation
“…12 Based on research in Tangerang and Jakarta, Subahar et al, examined house dust and found 66.9% house dust mites positive and identified as Dermatophagoides pteronyssinus, Dermatophagoides farina, and Glyciphagus destructor. 13 Based on research in Pekanbaru found all of the atopic dermatitis patients' residences were house dust mites positive. 14 House dust mites are found all over the world.…”
Section: Introductionmentioning
confidence: 99%